The World Is Not Yet Flat : Transport Costs Matter! - Behrens, Kristian; Brown, W. Mark; Bougna, Theophile (The MIT Press, 2018)
Using micro-level commodity flow data and micro-geographic plant-level data, we construct industry-specific ad valorem trucking rate series and measures of geographic concentration to provide evidence on the relationship between transport costs and agglomeration. We find that low transport cost industries display significantly more geographic concentration in the cross-sectional dimension, and that falling transport costs agglomerate industries in the panel dimension. The effects are large: the fall in trucking rates between 1992 and 2008 implied a 20% increase in geographic concentration on average, all else equal.